The Influence of Organizational Culture, Career Expectations, and Leadership Beliefs On Achievement Motivation In Integrated Islamic Primary Schools Riau Islands Province - Nurhayati Nurhayati; Mukhtar Latif; Kasful Anwar (Dinasti International Journal of Education Management And Social Science, 2024)
In this research the author used quantitative research methods with a sample size of 116 respondents from SDIT Darussalam, SDIT Al-Madinah, SDIT Scholar. The data collection method used is in the form of a questionnaire which is then processed with statistical analysis. The results include; 1). Organizational culture has a direct effect on achievement motivation by 9.7%. 2). Career Expectations have a direct effect on Achievement Motivation by 24.4%. 3). Organizational Culture and Career Expectations simultaneously have a direct effect on Achievement Motivation by 29.1%. 4). Organizational culture has a direct effect on Leadership Trust by 13.9%. 5). Career Expectations have a direct effect on Leadership Confidence by 16.7%. 6). Organizational Culture and Career Expectations simultaneously have a direct effect on Leadership Trust by 25.6%. 7). Leadership Trust has a direct effect on Achievement Motivation by 36.2%. 8) Organizational Culture, Career Expectations and Leadership Trust together (simultaneously) have a direct effect on Achievement Motivation by 44.4%. 9). Organizational Culture has a direct effect on Achievement Motivation through Leadership Trust by 41%. 10). Career Hope has a direct effect on Achievement Motivation through Leadership Trust by 41.5%. The conclusion is that organizational culture, career expectations and leadership beliefs can influence achievement motivation.